Cognitive Support Increase CD4 Level on Patient with HIV at Kota Kediri - Yuly Peristiowati; Sandu Siyoto; Ratna Wardani (Universitas Airlangga, 2015)
Introduction: HIV still becomes health problem that threaten Indonesia and many countries around the world. When HIV enters the body, it looks for CD4 cells and begins to replicate itself. Once replicated and left the dead CD4, the new viral particles will be looking for and infecting new CD4. The purpose of this study was to determine the effects of cognitive supports on CD4 level people living with HIV. Those cognitive supports consist of information, psychological, and spiritual support in order to increase the levels of CD4.Methods: This was quasy experiment research with posttest group design. Population were all people living with HIV at Kota Kediri. Samples were 20 respondents who meet the criteria, divided into two groups, intervention and control. The independent variable was cognitive support, while dependent variable was CD4 level of people living with HIV. Blood samples were collected to examine CD4 level. Data were then analyzed by using Anova test and T-test.Results: Results indicated that the cognitive supports had an effect in increasing the levels of absolute CD4 and CD4 percentage of people living with HIV at a signifi cance value of 0.003. However, there was no signifi cant difference between the control groups taking ARV regularly and irregularly.Conclusion: The provision of cognitive support was capable to stimulate the immune system by increasing T lymphocytes that have CD4 molecular markers. Thus, an increase in the levels of CD4 is expected to improve the quality of life of people living with HIV.